Opportunities for early diagnostics of contemporary obstetric sepsis - V. F. Bezhenar; V. A. Shapkaitz; I. A. Dobrovolskaya; E. A. Rukoyatkina; I. M. Nesterov (IRBIS LLC, 2021)
Aim: to objectively assess potential for early generalized postpartum infection diagnostics prior to the onset of irreversible organ changes based on a retrospective analysis.Materials and Methods. Сlinical and laboratory forensic medical data were examined by analysing 29 cases of severe maternal outcomes coupled to sepsis: including 17 «near miss» and 12 deceased patients (maternal mortality). The control group consisted of 30 patients who had chorioamnionitis in labor and successfully completed pregnancy. Statistical data analysis was carried out by using nonparametric statistics by creating conjugacy tables and assessing a relationship between parameters with Pearson χ2 distribution.Results. There were found significant differences in rate of some symptoms in both groups. Patients with severe maternal outcomes vs. control group were significantly more likely to develop hyperthermia ≥ 38.0 °C or hypothermia ≤ 36.0 °C, hectic fever, leukocytosis ≥ 12×109/L or leukopenia ≤ 4×109/L before the end of pregnancy; after pregnancy, persistent subfebrility, febrility or hypothermia, hectic fever, multiple-organ failure syndrome (PON), as well as uterine subinvolution and abnormal discharge from the genital tract were observed.Conclusion. Early identification of recognized symptoms of systemic inflammatory response syndrome and PON allows to properly assess severity of patient condition, taking into account the risk of generalized infection, contributes to making correct diagnosis and timely implementation of adequate organizational and therapeutic measures.